Morphological and dermatoglyphic analysis on a female juvenile bodybuilding athlete (Research, Society and Development, 2022)
Considering that contemporary researches have rescued and adapted anthropometric resources in bodybuilding, as well as presented results that stimulate the modality to be better investigated, this study aimed to monitor the morphological characteristics of a first-time contender and, in addition, identify, via dermatoglyphics, her genetic predisposition. Methodology: Our work is a case study. Results: The somatotype in the off-season period was classified as Endomorphic Mesomorphic, while in the pre-contest, as Ectomorphic Mesomorph; it also presented a statistically significant distance, either in the dispersion distance or in the spatial distance of the somatotype. The endomorphic component altered its interpretation, going from moderate to low, as well as the ectomorphy, interpreted as low in one of the off-season periods, was seen as moderate in the competition. Regarding body composition, despite having a reduction, both in total mass and fat mass, there was an increase in muscle mass. Even though being considered a perimetric involution, an increase occurred in the lean area of the arm and leg. Dermatoglyphics indicated the predominance for glycolytic fibers, with a higher percentage in type IIb. Conclusion: We conclude, from the previous findings corroborated in the present intervention, that while dermatoglyphics has identified genetic predispositions consistent with the requirements of certain divisions, anthropometry has been able to monitor variables also considered fundamental for a victorious career in this sport. Obviously, it is necessary to repeat these conclusions in subsequent studies, which mainly consider the sample number and the competitive level of sportsperson.